2010
DOI: 10.1007/s10886-010-9763-9
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Phenolic Glycosides by Quaking Aspen (Populus tremuloides) Leaves in Relation to Extrafloral Nectaries and Epidermal Leaf Mining

Abstract: We studied the effect of epidermal leaf mining on the leaf chemistry of quaking aspen, Populus tremuloides, during an outbreak of the aspen leaf miner, Phyllocnistis populiella, in the boreal forest of interior Alaska. Phyllocnistis populiella feeds on the epidermal cells of P. tremuloides leaves. Eleven days after the onset of leaf mining, concentrations of the phenolic glycosides tremulacin and salicortin were significantly higher in aspen leaves that had received natural levels of leaf mining than in leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…First, reduced photosynthesis due to leaf mining, combined with the cost of mounting an induced defense in response to herbivore damage, might compete for nutrients with leaf expansion (Dale 1988). Several defensive compounds are inducible by foliar damage in aspen, including phenolic glycosides (Clausen et al 1991;Young et al 2010), tannins (Stevens and Lindroth 2005), and trypsin-inhibiting compounds (Haruta et al 2001). Second, reduction in leaf size may be a direct consequence of induced defense.…”
Section: Discussionmentioning
confidence: 99%
“…First, reduced photosynthesis due to leaf mining, combined with the cost of mounting an induced defense in response to herbivore damage, might compete for nutrients with leaf expansion (Dale 1988). Several defensive compounds are inducible by foliar damage in aspen, including phenolic glycosides (Clausen et al 1991;Young et al 2010), tannins (Stevens and Lindroth 2005), and trypsin-inhibiting compounds (Haruta et al 2001). Second, reduction in leaf size may be a direct consequence of induced defense.…”
Section: Discussionmentioning
confidence: 99%
“…The aspen blotch miner Phyllonorycter salicifoliella (Lepidoptera, Gracillariidae) avoids exposure to high levels of salicinoids by selectively feeding on poplar species with low levels of salicinoids such as Populus tremuloides (Auerbach & Alberts, ). Recent studies show that the extent of damage by aspen blotch miners is indeed negatively correlated to the total salicinoid concentration of P. tremuloides leaves (Young et al , 2010 a , b ). Leaf‐mining Scaptomyza flava (Diptera, Drosophilidae) larvae exhibit significantly reduced growth rates on glucosinolate‐containing wild‐type A. thaliana relative to larvae reared on plants with low levels of glucosinolates (Whiteman et al , ).…”
Section: From Feeding To Digestion: Targets For Insect Herbivore Adapmentioning
confidence: 99%
“…Several studies have shown that phenolics can be induced by herbivores (e.g., Boege 2004, Stevens and Lindroth 2005, Kaplan et al 2008, Pascual-Alvarado et al 2008). In the future it would be useful to determine whether phenolics are induced in V. vitis-idaea by performing an insect removal experiment such as the one Young et al (2010) did with aspen and leaf miners.…”
Section: Secondary Chemistrymentioning
confidence: 99%